One In The Same. Skriðuklaustur: A Medieval Icelandic Monastery Following In The Christian Tradition - McDougall, Ashlie E., 1990- (2015)
This is a study in the medieval Christian tradition and how it played out across distance and physical boundaries. It is meant to explore how Skriðuklaustur, a monastery in Iceland, is an example of how far reacting Christianity was at the time. The differences and similarities to other monasteries at the time are discussed and shown through the lens of their symbolic meanings as opposed to their face value. The first step is to study the layout of the monasteries and how deviation from the accepted layout affected the monastery. Secondly, the building materials are examined and explored in their geographical context. Lastly, the hospital of Skriðuklaustur is observed and tied into the traditional monastic hospitals of the time. In the conclusion the importance is placed on how the differences and similarities tie Skriðuklaustur into the Christian monastic institution despite the isolated location. The goal is to challenge how physicality separates monasteries that follow the customs within their own boundaries.